Anti-inflammatory effect of lavender (Lavandula angustifolia Mill.) essential oil prepared during different plant phenophases on THP-1 macrophages - Edina Pandur; Alex Balatinácz; Giuseppe Micalizzi; Luigi Mondello; Adrienn Horváth; Katalin Sipos; Györgyi Horváth (BMC, 2021)
Abstract Background Pseudomonas aeruginosa is the most common Gram-negative bacterium associated with nosocomial respiratory infections. Lavender essential oil is mainly used in aromatherapy, but it has several pharmacological and therapeutic properties. Furthermore, it possesses antifungal and antibacterial activities. The anti-inflammatory activity of essential oils may depend on the composition and the ratio of the compounds. The constitution of the essential oils extracted from the different stages of flowering period varies, which makes it plausible that the collection time of the flowers influences the anti-inflammatory effects. Different types of essential oils reduce inflammation acting similarly by modulating the activity and action of the NFκB signalling pathway, which is the major regulator of the transcription of pro-inflammatory cytokines. Methods Lavender essential oils were distilled from lavender plant cultivated in Hungary and the flowers were harvested at the beginning and at the end of flowering period. The experiments were carried out on THP-1 human monocyte/macrophage cell line as in vitro cell culture model for monitoring the effects of lavender essential oils and the main compound linalool on P. aeruginosa LPS stimulated inflammation. The mRNA and protein levels of four pro-inflammatory cytokines, IL-6, IL-1β, IL-8 and TNFα were determined by Real Time PCR and ELISA measurements. The effects of essential oils were compared to the response to two NFκB inhibitors, luteolin and ACHP. Results Linalool and lavender essential oil extracted from plants at the beginning of flowering period were successful in decreasing pro-inflammatory cytokine production following LPS pretreatment. In case of IL-8 and IL-1β lavender oil showed stronger effect compared to linalool and both of them acted similarly to NFκB inhibitors. Pretreatments with linalool and lavender essential oil/beginning of flowering period prevented pro-inflammatory cytokine production compared to LPS treatment alone. Although lavender essential oil/end of flowering period decreased IL-6, IL-1β and IL-8 mRNA expression in case of LPS pretreatment, it was not capable to reduce cytokine secretion. Conclusion Based on our results it has been proven that lavender essential oil extracted at the beginning of flowering period is a potent inhibitor of the synthesis of four pro-inflammatory cytokines IL-6, IL-8, IL-β and TNFα of THP-1 cells. This supports the relevance of the collection of the lavender flowers from early blooming period for essential oil production and for the utilization as an anti-inflammatory treatment.